Decompensated Heart Failure in a 10-Year-Old Male: A Case of Rheumatic Heart Disease with Severe Mitral Regurgitation and Pulmonary Hypertension - Puteri Kemala Indah Fedina; Puteri Reno Fadila; Puteri Ayudia Fadita (International Medical Journal Corp. Ltd, 2025)
Introduction: Rheumatic Heart Disease (RHD) remains a principal cause of acquired heart disease and subsequent heart failure among children and young adults in developing nations, despite being largely preventable. This report details a case of advanced RHD presenting as decompensated heart failure in a pediatric patient, highlighting the severe consequences of the disease. Case Illustration: A 10-year-old male presented with a two-month history of progressive abdominal distension, dyspnea on exertion, and lower limb edema. Physical examination was significant for hypertension, tachycardia, a pansystolic murmur, ascites, and bilateral pitting edema. A comprehensive diagnostic workup confirmed the clinical suspicion. Electrocardiography revealed sinus tachycardia and left atrial enlargement (P mitrale). Chest radiography demonstrated marked cardiomegaly. Transthoracic echocardiography was pivotal, identifying severe mitral regurgitation secondary to anterior mitral leaflet prolapse, severe left atrial dilation, and a high probability of pulmonary hypertension. Pertinent laboratory findings included mild anemia, leukocytosis, hypokalemia, borderline hypoalbuminemia, and proteinuria. Discussion: The patient's clinical presentation is a classic manifestation of chronic volume and pressure overload resulting from severe mitral regurgitation, which has culminated in biventricular failure. The discussion explores the pathophysiological cascade from valvular incompetence to systemic congestion, the significance of the counterintuitive finding of hypertension in decompensated heart failure, and the multi-organ involvement indicated by the laboratory abnormalities. The management strategy, employing guideline-directed medical therapy with diuretics, renin-angiotensin-aldosterone system inhibitors, and beta-blockers, is detailed. Conclusion: This case underscores the devastating consequences of untreated or recurrent acute rheumatic fever. It highlights the critical and urgent need for robust primary and secondary prevention strategies for RHD, particularly in endemic regions such as Indonesia, to avert preventable morbidity and mortality in the young.